Analysis of kerogens and model compounds by time-of-flight secondary ion mass spectrometry (TOF-SIMS). (15th February 2021) - Sjövall, Peter; Bake, Kyle D.; Pomerantz, Andrew E.; Lu, Xiaohu; Mitra-Kirtley, Sudipa; Mullins, Oliver C.
Abstract: Here, kerogens of differing heat treatments are subjected to extremely high dissociation energies by sample bombardment by 25 keV Bi3 + primary ions during analysis by time-of-flight secondary ion mass spectrometry (TOF-SIMS). Positive and negative secondary ions are produced from this decomposition and fragment ion distributions of model compounds and kerogens are compared and starkly different results are obtained for cations versus anions. Cations exhibit a large range of C/H ratios and include highly unsaturated linear chain ions and aromatic ions. Cations of kerogens possess predominantly no heteroatoms. Positive fragment ion distributions depend on the source material being bombarded. Mature, more aromatic kerogens produce higher yields of fragment ions of highly unsaturated carbon chains while immature, more aliphatic kerogens produce more aromatic fragment ions, particularly at the higher carbon numbers. This is consistent with the observation that aromatic model compounds produce a greater fraction of hydrogen-deficient, carbon chain fragment ions, as compared to a purely aliphatic model compound. There is substantial suppression of free radical fragment cations, except for large fragments. In contrast, there is little free radical suppression of the anions. The anions tend to be very hydrogen deficient, spanning a small range of C/H ratios. Highly unsaturated to pure carbon chain fragment anions dominate while aromatic anions are not found. In both positive and negative ion spectra, the yields of fragment ions corresponding to derivatives of the carbon chain molecules, polyynes and allenes, are substantial. Some heteroatom-containing fragment anions are produced, all of which are very hydrogen deficient.